M is for malice eaudiobook - Grafton, Sue (Kinsey Millhone, 2007)
4 cassettes / 4 hours Read by Judy Kaye "There are few writers able to sustain the solid mixture of detection, narrative energy and cultural observations that one finds in Grafton." — Washington Post Book World "M" is for money.  Lots of it.   "M" is for Malek Construction, the $40 million company that grew out of modest soil to become one of the big three in California construction, one of the few still in family hands. "M" is for the Malek family: four sons now nearing middle age who stand to inherit a fortune - four men with very different outlooks, temperaments, and needs, linked only by blood and money.  Eighteen years ago, one of them - angry, troubled, and in trouble - went missing. "M" is for Millhone, hired to trace that missing black sheep brother. "M" is for memories, none of them happy.  The bitter memoirs of an embattled family.  This prodigal son will find no welcome at his family's table.   "M" is for malice. And in brutal consequence, "M" is for murder, the all-too-common outcome of familiar hatreds. "M" is for malice . . . and malice kills.